2018
DOI: 10.3892/mmr.2018.9262
|View full text |Cite
|
Sign up to set email alerts
|

‘Psoriasis 1’ reduces psoriasis‑like skin inflammation by inhibiting the VDR‑mediated nuclear NF‑κB and STAT signaling pathways

Abstract: ‘Psoriasis 1’, a Chinese herbal medicine (CHM) formulation, is extensively used to treat psoriasis in China. Although this CHM formulation yields good therapeutic effect, the underlying mechanism of how this works remains unknown. The present study aimed to test the hypothesis that the CHM formulation ‘psoriasis 1’ inhibits vitamin D receptor (VDR)-mediated inflammation in psoriasis. To test this, a model of psoriasis was established by stimulating keratinocytes (HaCaT cells) with tumor necrosis factor (TNF)-α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…To verify anti-inflammatory regulation of human skin by brazilin, we used a TNF-α induced HaCaT cell as a psoriasis dermatitis in vitro test model [16][17][18]. First, we performed RT-PCR to determine mRNA expression levels of IL-1α, IL-1β, IL-6, IL-8, TNF-α and COX-2 genes as pro-inflammatory cytokines related to psoriasis dermatitis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To verify anti-inflammatory regulation of human skin by brazilin, we used a TNF-α induced HaCaT cell as a psoriasis dermatitis in vitro test model [16][17][18]. First, we performed RT-PCR to determine mRNA expression levels of IL-1α, IL-1β, IL-6, IL-8, TNF-α and COX-2 genes as pro-inflammatory cytokines related to psoriasis dermatitis.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, IL-6, IL-17, IL-22, and transforming growth factor beta (TGF-β) expressed in Th17 cells accelerate psoriatic lesion's inflammatory reaction by activating STAT (Signal Transducer and Activator of Transcription) [13][14][15]. Accordingly, TNF-α inhibitor is most widely used at present as a medicine for psoriasis dermatitis, and TNF-α treated keratinocyte has been used as a psoriasis dermatitis test model in many in vitro studies [16][17][18]. When TNF-α binds to TNFR (Tumor Necrosis Factor Receptor) in keratinocyte, Akt (Protein kinase B) and IKK (I-κB kinase) protein is activated to phosphorylate I-κB (Inhibitors kappa B), which then activates NF-kB.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that TLR4 is critical for the activation of NF-κB and the subsequent production of pro-inflammatory cytokines that are implicated in a variety of diseases (19)(20)(21). As a transcription factor, NF-κB serves vital roles in numerous processes, including inflammation, immunity and cell proliferation (22). NF-κB is an important signaling pathway in the development of a number of inflammation-mediated diseases, including pediatric bronchial asthma (23).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the widely acknowledged histopathological features of psoriasis include four major aspects: the inflammatory infiltration in dermis and epidermis, the abnormal biological behaviours (differentiation, hyperproliferation, and apoptosis) of keratinocytes, metabolic disturbance in skin tissue, and the tortuously increased dermal blood vessels and capillaries [37][38][39][40][41]. Firstly, among the 27 core targets, most of them (PTGS2, ILs, JAK2, STAT3, RELA, CCL2, CXCL8, EGF, IFNG, and TLR4) have been shown to be involved in abnormal inflammatory infiltration, which could regulate the differentiation and chemotaxis of lymphocytes, cytokines produced, and immunological inflammatory reaction in dermis and epidermis [42][43][44][45][46][47][48]. Secondly, RELA, MAPKs, JUN, and BCL2L1 are associated with the aberrant biological behaviours of keratinocytes in psoriasis [49][50][51].…”
Section: Discussionmentioning
confidence: 99%